AnalisisEffect of Ethanol–LPG Dual Fuel on Output Voltage Stability of a Four-Stroke Generator - Witanto, Yovan; Nuramal, Agus; Pratama, Samuel Yoga; Helmizar, Helmizar; Rosa, Khairul Amri (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the effect of load variation on the output voltage of a modified four-stroke generator using a dual-fuel system consisting of ethanol and liquefied petroleum gas (LPG). Ethanol 96% was used as the primary fuel, while LPG was injected through an ideal mixture screw with the aid of a converter kit, pressure regulator, and flowmeter to control gas flow. The test subject was a modified Yasuka 1500DC gasoline generator. Experiments were conducted using incandescent lamp loads ranging from 200 to 1000 watts, in 200-watt intervals, each applied for 2 minutes at a constant engine speed. The observed parameters included fuel consumption and output voltage. The LPG flow rates tested were 0.2, 0.4, 0.6, and 0.8 liters per minute. The results showed that the ethanol–LPG combination at a flow rate of 0.8 l/min produced the highest and most stable voltage output, remaining above the safe threshold of 198 volts. Compared to pure ethanol or gasoline, the dual-fuel system was more effective in maintaining voltage under high load conditions. This is attributed to LPG’s high calorific value and its ease of mixing with air, which enhances combustion quality.